Cytotoxic oplopane sesquiterpenoids from Arnoglossum atriplicifolium. Issue 18 (16th September 2016) - Clement, Jason A.; Bleich, Rachel M.; Campbell, Hailey E.; Naylor, Kristin; Flood, Matthew J.; Kelly, Ryan M.; Wu, Shi-Biao; Kennelly, Edward J.; Schmitt, Jeffrey D.
Abstract: Pale Indian plantain ( Arnoglossum atriplicifolium (L.) H. Rob.) is a plant with traditional medicinal usage among the Cherokee Native American tribe for treating cancer. Two oplopane sesquiterpenoids were isolated from an extract of A. atriplicifolium from Western North Carolina. The compounds were isolated by bioassay-guided fractionation using an MCF-7 breast tumour cell line assay. The known compound (1 S, 6 R, 7 R, 8 R )-1-acetoxy-6, 7-diangeloxy-8, 10-epoxy-2-oxo-oplopa-3, 14Z, 11, 12-dien-13-al (1 ) had an EC50 value of 9.0 μM against MCF-7 cells, while the new compound (1 S, 3 R, 6 R, 7 R, 8 R, 11 S )-1-acetoxy-6, 7-diangeloxy-8, 10, 11, 13-bisepoxyoplopan-2-one (2 ) had an EC50 value of 96 μM. The compounds were characterised by 1D and 2D NMR spectroscopy and by comparison with literature values in the case for1 . Based on NOESY analysis, a correction of the relative configuration for1 is presented. The presence of these compounds may help to explain the folk remedy usage of this plant as an anticancer agent. Abstract :